Establishing a Standard Method for Screening Lymphatic Ultrasound in Lymphedema Patients - Hisako Hara, MD, PhD; Makoto Mihara, MD (Plastic and Reconstructive Surgery, Global Open, 2025)
Background:. Lymphatic ultrasound (LU) is a valuable tool for treating lymphedema, but no detailed protocol exists. This study aimed to establish a standardized method for screening LU. Methods:. We analyzed LU images from 70 limbs of 35 patients with lower extremity lymphedema (1 man, 34 women; mean age 66.5 y). An 18-MHz linear probe was used, and the D-CUPS (Doppler, crossing, uncollapsible, parallel, superficial fascia) index identified lymphatic vessels. Images were taken at 5 cm (T5) and 10 cm (T10) distal to the saphenofemoral junction and at 5 cm (C5) and 10 cm (C10) distal to the popliteal fossa. Distances between the great saphenous vein (GSV) and lymphatic vessels were measured. Vessel diameters were assessed, and a receiver operating characteristic curve determined the cutoff value for distinguishing normal from dilated lymphatic vessels. Results:. At T5 and T10, lymphatic vessels were identified in 62 limbs (88.6%), with average distances of 17.3 and 15.5 mm lateral to the GSV, respectively. At C5 and C10, vessels were identified in 53 limbs (75.7%), with distances of 12.6 and 13.9 mm medial to the GSV. The receiver operating characteristic curve yielded an area under the curve of 0.83, with a cutoff of 0.25 mm for differentiating normal and dilated vessels. Conclusions:. Lymphatic vessels are generally lateral to the GSV in the thigh and medial to the GSV in the calf. These findings simplify vessel identification, enabling broader use of LU for assessing lymphatic function.